Implementation of Law No. 23 of 2004 on the Elimination of Domestic Violence Domestic Violence (PKDRT) in the Province of North Sumatra - Mutiara, Mutiara; Syofiaty Lubis (Dinasti Research, 2024)
Implementation of Law no. 23 of 2004 concerning the elimination of domestic violence aims to prevent and overcome the occurrence of domestic violence. The article states that acts of domestic violence are a form of criminal act. Criminal threats for perpetrators of domestic violence have been regulated in Law no. 23 of 2004. The National Commission for Women's Protection is a national institution that highlights acts of domestic violence. Komnas Perempuan makes various efforts to prevent cases of domestic violence. Komnas Perempuan collaborates with various state institutions and community institutions to prevent cases of domestic violence. Apart from that, Komnas Perempuan also regularly issues CATAHU (annual records) and provides training and campaigns to prevent and suppress cases of domestic violence.